Synthesis and characterizations of peripheral octa-amino and octa-amidophthalocyanines - Yüksel, Fatma; Tuncel, Sinem; Ahsen, Vefa (World Sci Publ Co Inc, 2008)
Novel 2-,3,9,10,16,17,23,24-octaamino substituted Ni(II) phthalocyanine (2) was synthesized from tosylamido (tosyl: toluene-p-sulphonyl) derivative by the cleavage of tosyl groups in the presence of 90% Sulfuric acid. Octa-hexanoylamido Ni(II) phthalocyanine (3a) and octa-lauroylamido Ni(II) phthalocyanine (3b) were obtained by reacting of octa-amino Ni(II) phthalocyanine (2) with hexanoyl chloride and lauroyl chloride, respectively. The new compounds have been characterized by elemental analysis, FT-IR, NMR and UV-vis spectroscopy and mass spectrometry. The aggregation behaviors of new compounds were investigated by UV-vis Spectroscopy. Copyright (C) 2008 Society of Porphyrins & Phthalocyanines.
Keywords: phthalocyanine; octa-aminophthalocyanine; octa-amidophthalocyanine